2014
DOI: 10.1108/ijpcc-01-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the usability of touch-based and mouse-based interaction

Abstract: A comparative study of the usability of touch-based and mouse-based interaction Charlotte Travis Pietro Murano Article information:To cite this document: Charlotte Travis Pietro Murano , (2014),"A comparative study of the usability of touch-based and mousebased interaction"If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…Furthermore, data collected from homogeneous types of users cannot be generalized [ 19 ], therefore, the participants were divided into three groups, i.e., experts, intermediate skilled, and novices based on MS Word usage. Similar categorization is used in the studies [ 5 , 24 , 29 ] as well. The participants with more than five years of experience were categorized as experts and up to five years of experience were categorized as intermediate skilled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, data collected from homogeneous types of users cannot be generalized [ 19 ], therefore, the participants were divided into three groups, i.e., experts, intermediate skilled, and novices based on MS Word usage. Similar categorization is used in the studies [ 5 , 24 , 29 ] as well. The participants with more than five years of experience were categorized as experts and up to five years of experience were categorized as intermediate skilled.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 also indicates which type of tasks can be executed with accuracy or efficiency with what type of device. For example, [ 5 – 7 , 10 , 17 , 22 – 24 ] suggested that tasks such as drawing, use of a list box, selection from dropdown list box, selecting up/down button, steering tasks, drag and drop, point, click, tracing, and selecting tasks can be executed with more accuracy with a mouse and efficiently with a touchscreen. Some tasks’ execution in terms of accuracy and efficiency are comparable when the selection of a device is a concern.…”
Section: Related Workmentioning
confidence: 99%
“…Hal lain yang perlu diperhatikan adalah input dari suatu perangkat. Input yang digunakan dapat mempengaruhi performa, bahkan kepuasan dari seseorang saat mengerjakan suatu kegiatan ( (Travis & Murano, 2014); (Chung & Shin, 2015)). …”
Section: Penelitian Terkaitunclassified
“…As a result, many researchers and practitioners have become concerned with the utilization of touch interfaces (Im et al, 2015;Radhakrishnan et al, 2013;Travis and Murano, 2014). A touch interface reflects the behavior of users in real-world situations and also provides a convenient method to complete information search and input tasks (Benko et al, 2006).…”
Section: Introductionmentioning
confidence: 99%